Ce0.97Cu0.03O2 Nanocatalysts Synthesized via Microwave-assisted Hydrothermal Method: Characterization and CO-PROX Catalytic Efficiency - Araújo, Vinícius Dantas de; Avansi, Waldir [UNESP]; Mascarenhas, Artur J.s.; Andrade, Heloysa M.c.; Bernardi, Maria I.b.; Silva, Elson Longo da [UNESP] (Springer Nature, 2013)
In the work presented here, Ce0.97Cu0.03O2 nanoparticles were synthesized by a microwave-assisted hydrothermal method under different synthesis temperatures. The obtained nanoparticles were tested as catalysts in preferential oxidation of CO to obtain CO-free H2 (PROX reaction). The samples were characterized by X-ray diffraction, transmission electron microscopy (TEM), electron paramagnetic resonance spectroscopy (EPR) and temperature-programmed reduction (TPR). X-ray diffraction measurements detected the presence of pure cubic CeO2 for all synthesized samples. TEM images of the Ce0.97Cu0.03O2 nanoparticles revealed that samples synthesized at 80°C are composed mainly of nanospheres with an average size of 20 nm. The formation of some nanorods with an average diameter of 8 nm and 40 nm in length, and the size reduction of the nanoparticles from 20 to approximately 15 nm is observed with increasing synthesis temperature. EPR spectra indicated that copper is found well dispersed in sample synthesized at 160°C, located predominant in surface sites of ceria. For samples synthesized at 80 and 120°C, the species are less dispersed than in the other one, resulting in the formation of Cu2+−Cu2+ dimmers at the surface of ceria. TPR profiles presented two reduction peaks, one below 400°C attributed to the reduction of different copper species and a second peak around 800°C attributed to the reduction of Ce4+→ Ce3+ species located in the volume of the nanoparticles. The peak related to the reduction of copper species shifts to lower temperatures with increasing synthesis temperature, i.e., the sample synthesized at 160°C is more easily reduced than the ones synthesized at 120 and 80°C. The nanoparticles showed active as catalysts for the CO-PROX reaction. The microwave-assisted method revealed efficient for the synthesis of Ce0.97Cu0.03O2 nanoparticles with copper species selective for the CO-PROX reaction, which reaches CO conversions up to 92% for the sample synthesized at 160°C.
Keywords: catalytic; chemical synthesis; nanostructure